Stability study of PD and PI controllers in multiple difference disturbances - M.A. Nur, Huda; Hyreil Anuar, Kasdirin; Mohd Ruddin, Ab Ghani (2012)
This paper discusses the stability study of PD and Pl controllers in multiple difference disturbances. The multiple difference disturbances in this paper are added to the inverted pendulum model that based on robotic leg application such as pendubot. By applying the pendubot model via MATLAB/Simulink block diagram, the performances between the model and disturbances are compared for stability in the simulation results. The simulation results showed that the PD controller could reduce and eliminate disturbances more effective than PI controller in the pendubot model. Overall, the simulation results are based on stability analysis for the degree of stability, steady state performance and transient response.